Clinical Interpretation of Drug Susceptibility Tests in Tuberculosis - Laniado-Laborín, Rafael (Current Respiratory Medicine Reviews, 2020)
Prompt and accurate diagnosis of drug resistance is essential for optimal treatment of drug-resistant tuberculosis. However, only 20% of the more than half a million patients eligible for the treatment of MDR-TB/RR-TB receive an appropriate drug regimen. Drug-resistant TB regimens must include a sufficient number of effective medications, a significant challenge for clinicians worldwide, as most are forced to make therapeutic decisions without any, or very little information on drug susceptibility testing. Although phenotypic DST is still commonly regarded as the gold standard for determining M. tuberculosis susceptibility to antituberculosis drugs, it has several limitations, mainly its prolonged turnaround time. Molecular methods based on M. tuberculosis genomic DNA sequencing have been developed during the past two decades, to identify the most common mutations involved in drug resistance. The Xpert ® MTB/RIF is a real-time polymerase chain reaction that offers results in less than two hours and has an overall sensitivity for rifampin resistance of 96% and 98% specificity. Line probe assays (LPAs) are commercial DNA strip-based tests for detecting the most frequent mutations responsible for resistance to rifampin, isoniazid, fluoroquinolones, and second-line injectable drugs. Discrepancies between phenotypic and genotyping methods are a problem that the clinician will face in everyday practice. However, any resistance result (with any type of test) in a person with risk factors for harboring resistant microorganisms should be considered appropriate while the results of complementary tests are available.
Keywords: heteroresistance